The Contribution of Spinal Glial Cells to Chronic Pain Behaviour in the Monosodium Iodoacetate Model of Osteoarthritic Pain. Issue 1 (17th November 2011) - Sagar, Devi Rani; Burston, James J; Hathway, Gareth J; Woodhams, Stephen G; Pearson, Richard G; Bennett, Andrew J; Kendall, David A; Scammell, Brigitte E; Chapman, Victoria
Background: Clinical studies of osteoarthritis (OA) suggest central sensitization may contribute to the chronic pain experienced. This preclinical study used the monosodium iodoacetate (MIA) model of OA joint pain to investigate the potential contribution of spinal sensitization, in particular spinal glial cell activation, to pain behaviour in this model. Experimental OA was induced in the rat by the intra-articular injection of MIA and pain behaviour (change in weight bearing and distal allodynia) was assessed. Spinal cord microglia (Iba1 staining) and astrocyte (GFAP immunofluorescence) activation were measured at 7, 14 and 28 days post MIA-treatment. The effects of two known inhibitors of glial activation, nimesulide and minocycline, on pain behaviour and activation of microglia and astrocytes were assessed. Results: Seven days following intra-articular injection of MIA, microglia in the ipsilateral spinal cord were activated (p < 0. 05, compared to contralateral levels and compared to saline controls). Levels of activated microglia were significantly elevated at day 14 and 21 post MIA-injection. At day 28, microglia activation was significantly correlated with distal allodynia (p < 0.05). Ipsilateral spinal GFAP immunofluorescence was significantly (p < 0.01) increased at day 28, but not at earlier timepoints, in the MIA model, compared to saline controls. Repeated oral dosing (days 14-20) with nimesulide attenuated pain behaviour and the activation of microglia in the ipsilateral spinal cord at day 21. This dosing regimen also significantly attenuated distal allodynia (p < 0.001) and numbers of activated microglia (p < 0.05) and GFAP immunofluorescence (p < 0.001) one week later in MIA-treated rats, compared to vehicle-treated rats. Repeated administration of minocycline also significantly attenuated pain behaviour and reduced the number of activated microglia and decreased GFAP immunofluorescence in ipsilateral spinal cord of MIA treated rats. Conclusions: Here we provide evidence for a contribution of spinal glial cells to pain behaviour, in particular distal allodynia, in this model of osteoarthritic pain. Our data suggest there is a potential role of glial cells in the central sensitization associated with OA, which may provide a novel analgesic target for the treatment of OA pain.